STRATEGI ADAPTASI USAHA LEMPUK DURIAN DI DESA SELATBARU KECEMATAN BANTAN KABUPATEN BENGKALIS - Handayani, Wahyu; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis. The purpose of this study was to determine the fabric artisans strategy lempuk durian maintain culture weaving in Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis. This study entitled " Adaptation Strategy of Lempuk Durian Business In Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis ". The focus of research focus is How Strategy Adaptation of durian lempuk business in desa Selatbaru kecamatan bantan kabupaten bengkalis.research topic what is the the population of this study is all Businessman Lempuk Durian in Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis. Population of this research is all Lempuk Durian Businessman. Sampling was done by sensus technique sampling. sample of 07 Lempuk Durian Businessman. The author uses descriptive qualitative method and the data were analyzed qualitatively. Instruments Data were observation, interviews and documentation.Adaptation Strategy Lempuk Durian Businessman in maintaining lempuk durian is as follows: Biologycal Investmen Strategy, this strategy made by lempuk durian businessman selatbaru by controlling the number of offspiring that the needsof the economy remains stable and craftsman do not need to find another job to cover the economic needs of the family because of the many family of members/children must be financed. Succesive Straregy, this Strategy is the most dominant strategy made the subjects of research in an effort to maintain business for direct inherited culture to the younger generations who will develop the teachings of his parents. Economy Investment Strategy, this strategy made weaving by maintaining the quality and quantity of woven lempuk durian. Is an effort to maintain the business of lempuk durian that is capital. The economic condition of entrepreneurs of durian slabs tend to be stable and sufficient. This is marked with the wisdom of the durian businessman in managing the income. Keywords: Businessman, Lempuk Durian, Culture